Nanoparticle delivery to metastatic breast cancer cells by nanoengineered mesenchymal stem cells - Saulite, Liga; Pleiko, Karlis; Popena, Ineta; Dapkute, Dominyka; Rotomskis, Ricardas; Riekstina, Una (Beilstein Journal of Nanotechnology, 2018)
We created a 3D cell co-culture model by combining nanoengineered mesenchymal stem cells (MSCs) with the metastatic breast cancer cell line MDA-MD-231 and primary breast cancer cell line MCF7 to explore the transfer of quantum dots (QDs) to cancer cells. First, the optimal conditions for high-content QD loading in MSCs were established. Then, QD uptake in breast cancer cells was assessed after 24 h in a 3D co-culture with nanoengineered MSCs. We found that incubation of MSCs with QDs in a serum-free medium provided the best accumulation results. It was found that 24 h post-labelling QDs were eliminated from MSCs. Our results demonstrate that breast cancer cells efficiently uptake QDs that are released from nanoengineered MSCs in a 3D co-culture. Moreover, the uptake is considerably enhanced in metastatic MDA-MB-231 cells compared with MCF7 primary breast cancer cells. Our findings suggest that nanoengineered MSCs could serve as a vehicle for targeted drug delivery to metastatic cancer.
Keywords: cancer; mesenchymal stem cells; quantum dots; spheroids; 3D cell culture